Yttrium oxide-aluminum oxide composite ceramic with high bonding strength as well as preparation method and application of yttrium oxide-aluminum oxide composite ceramic
The preparation of yttrium oxide-alumina composite ceramics through cold isostatic pressing process solved the problem of insufficient binding strength of the existing yttrium oxide coating, and realized yttrium oxide-alumina composite ceramics with high binding strength, satisfying high plasma power Protection requirements for lower etching machine components.
Patent Information
- Application Number
- CN202411565493.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-05
AI Technical Summary
The bond strength of the existing yttrium oxide etching-resistant coating and alumina substrate is poor, and the coating is prone to peeling off, which cannot meet the protection needs of etching machine components under high plasma power.
Yttrium oxide granulation powder and alumina granulation powder are used to prepare yttrium oxide-alumina composite ceramics through cold isostatic pressing process. Through vibration compaction and cold isostatic pressing technology, high-density, uniform structure molded ceramics are formed. and further enhance the strength by high temperature sintering.
The bonding strength of yttrium oxide-alumina composite ceramics is significantly improved, the coating peeling problem is solved, the protection function of alumina substrate is strengthened, and the use of etching machine components under high plasma power is met.
Smart Images

Figure CN119430878A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite ceramic preparation, and in particular to an yttria-alumina composite ceramic with high bonding strength and a preparation method and application thereof. Background Art
[0002] In the wafer manufacturing process, etching is essential; while etching the wafer with fluorine-containing plasma, it will inevitably corrode other alumina ceramic parts in the etching atmosphere, thereby reducing the service life of related alumina ceramic parts, and the etching products of other alumina ceramic parts will contaminate the wafer. To improve this problem, the existing technology usually prepares an etching-resistant coating on the surface of related parts; and yttrium oxide materials are widely used in etching-resistant coatings due to their excellent plasma tolerance and relatively economical production cost.
[0003] Among them, bonding strength is an important performance indicator of the etching-resistant coating. When the bonding strength of the coating is high, the coating is firmly bonded and not easy to fall off and fail. When the bonding strength of the coating is low, the coating is easy to fall off the substrate and lose its protectiveness. As the plasma power used by the etcher continues to increase, the impact force on the related components in the etcher cavity is gradually increasing, which places higher and higher requirements on the bonding strength between the coating and the alumina substrate. At present, the atmospheric plasma spraying method is often used to prepare yttrium oxide etching-resistant coatings, but the bonding strength between the yttrium oxide coating prepared by this method and the alumina substrate is poor, and the coating is prone to peeling. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention discloses an yttria-alumina composite ceramic with high bonding strength and a preparation method and application thereof, thereby solving or at least alleviating one or more of the above-mentioned problems and other problems in the prior art.
[0005] The present invention discloses a method for preparing an yttrium oxide-aluminum oxide composite ceramic with high bonding strength, comprising the following steps:
[0006] S1. Powder raw materials include yttrium oxide granulated powder and aluminum oxide granulated powder;
[0007] S2, first add a certain amount of alumina granulated powder into a forming mold of a cold isostatic press, and vibrate and compact the alumina granulated powder in the forming mold;
[0008] S3, adding a certain amount of yttrium oxide granulated powder into a molding die of a cold isostatic press, and vibrating and compacting the yttrium oxide granulated powder in the molding die;
[0009] S4, repeating steps S2 and S3 n times until the yttrium oxide granulated powder and the aluminum oxide granulated powder fill the entire molding die; wherein n≥0;
[0010] S5, placing the filled molding die into a cold isostatic press for cold isostatic pressing;
[0011] S6, machining the formed ceramic green body in step S5 to obtain at least one yttrium oxide-aluminum oxide composite ceramic green body, and machining the yttrium oxide-aluminum oxide composite ceramic green body into a designed shape, with the alumina portion serving as an alumina substrate and the yttrium oxide portion serving as a coating;
[0012] S7, transferring the yttrium oxide-aluminum oxide composite ceramic green body obtained in step S6 to a high-temperature sintering furnace for sintering, and naturally cooling to room temperature in the furnace to obtain the yttrium oxide-aluminum oxide composite ceramic.
[0013] Preferably, in step S1, the average particle size of the yttrium oxide granulated powder is 38 μm, and the average particle size of the aluminum oxide granulated powder is 57 μm.
[0014] Preferably, in step S3, position A and position B are respectively provided on the forming mold near its upper and lower ends, and an interface is formed between the alumina granulated powder and the yttrium oxide granulated powder, and the interface is located between position A and position B of the forming mold.
[0015] Preferably, in step S5, the cold isostatic pressing pressure P is 110-130 MPa.
[0016] Preferably, in step S5, the holding time m is 20-50s.
[0017] Preferably, in step S5, the holding time m is 20-30s.
[0018] Preferably, in step S7, the sintering process in the high temperature sintering furnace comprises the following steps:
[0019] S701: the heating rate V is 160-240℃ / min, the temperature is raised to 300℃, and the holding time is th; then the temperature is raised to 400℃ at the heating rate V, and the holding time is th; then the temperature is raised to 500℃ at the heating rate V, and the holding time is th; then the temperature is raised to the sintering temperature T of 1650℃ at the heating rate V, and the holding time is th; wherein, the range of t is 1-4h;
[0020] S702: The temperature is cooled from 1650°C to 1000°C at a cooling rate of 2°C / min, and then naturally cooled to room temperature along with the furnace.
[0021] Preferably, in step S701, the heating rate V is 160-200°C / min, and the holding time t is 2h.
[0022] In addition, the present invention provides yttrium oxide-aluminum oxide composite ceramics prepared by the above-mentioned preparation method of yttrium oxide-aluminum oxide composite ceramics with high bonding strength.
[0023] The yttria-alumina composite ceramic in the present invention has a relatively high bonding strength, and meets the application requirements of alumina ceramic parts, especially the use requirements of alumina ceramic parts working in the inner cavity of an etcher.
[0024] Furthermore, the present invention also provides the use of the yttria-alumina composite ceramic as described above in alumina ceramic parts in the inner cavity of an etcher.
[0025] The present invention has the following beneficial effects:
[0026] The technical scheme provides an yttrium oxide-aluminum oxide composite ceramic with high bonding strength and a preparation method and application thereof. Alumina granulated powder and yttrium oxide granulated powder are sequentially added into a molding mold and compacted by vibration. Then, the powder raw materials in the molding mold are uniformly pressurized by a cold isostatic pressing process. The powder raw materials are compressed in volume and pores are discharged to obtain a molded ceramic green body with uniform structure and high density. The molded ceramic green body is machined and then sintered to further improve the strength, thereby obtaining an integrally sintered yttrium oxide-aluminum oxide composite ceramic with high bonding strength. The problem of poor bonding strength and easy peeling of the yttrium oxide etching-resistant protective coating in the prior art is solved, while the protective function of the alumina substrate is strengthened. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the specific embodiments of the present disclosure, the following briefly introduces the drawings required for use in the specific embodiments. In all the drawings, each element or part is not necessarily drawn according to the actual scale.
[0028] Figure 1 It is a structural schematic diagram of a forming mold in a cold isostatic press of the present invention;
[0029] Figure 2 A diagram of a ceramic green body of the present invention;
[0030] Figure 3 This is a diagram of the yttria-alumina composite ceramic after sintering of the present invention;
[0031] Figure 4 This is an interface morphology diagram of the yttria-alumina composite ceramic prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0032] The following embodiments of the technical solution of the present disclosure are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present disclosure, and are therefore only used as examples, and cannot be used to limit the protection scope of the present disclosure.
[0033] It should be noted that, unless otherwise specified, the technical terms or scientific terms used in this application should have the common meanings understood by those skilled in the art to which the present invention belongs.
[0034] In the description of the present application, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the present invention.
[0035] In addition, the terms "first", "second", etc. are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0036] In this application, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0037] In the present application, unless otherwise clearly specified and limited, a first feature being “above” or “below” a second feature may mean that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. Moreover, a first feature being “above”, “above”, and “above” a second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being “below”, “below”, and “below” a second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.
[0038] A method for preparing a yttrium oxide-aluminum oxide composite ceramic with high bonding strength is provided in Examples 1-11 of the present invention. Specific parameters of the preparation process of the yttrium oxide-aluminum oxide composite ceramic are shown in Table 1.
[0039] A method for preparing an yttria-alumina composite ceramic with high bonding strength, comprising:
[0040] S1. The powder raw materials are yttrium oxide granulated powder and aluminum oxide granulated powder; the average particle size of the yttrium oxide granulated powder is 38 μm, and the average particle size of the aluminum oxide granulated powder is 57 μm;
[0041] S2, first add a certain amount of alumina granulated powder into a forming mold of a cold isostatic press, and vibrate and compact the alumina granulated powder in the forming mold;
[0042] S3, adding a certain amount of yttrium oxide granulated powder into the molding die of the cold isostatic press, and vibrating and compacting the yttrium oxide granulated powder in the molding die; the molding die is provided with a position A and a position B near the upper and lower ends thereof, respectively, and an interface is formed between the aluminum oxide granulated powder and the yttrium oxide granulated powder, and the interface is located between the position A and the position B of the molding die; Figure 1 As shown;
[0043] S4, repeating steps S2 and S3 n times until the yttrium oxide granulated powder and the aluminum oxide granulated powder fill the entire molding die; wherein n≥0;
[0044] S5, placing the filled molding mold into a cold isostatic press for cold isostatic pressing; the cold isostatic pressing pressure P is 110-130MPa, and the holding time m is 20-50s to obtain a molded ceramic green body; Figure 2 As shown; the powder raw materials in the forming mold are uniformly pressurized by cold isostatic pressing process, the powder raw materials are compressed in volume and the pores are discharged, so that a formed ceramic green body with uniform structure and high density can be obtained;
[0045] S6. Machining the formed ceramic green body to obtain at least one yttrium oxide-aluminum oxide composite ceramic green body, and machining the yttrium oxide-aluminum oxide composite ceramic green body into a designed shape, with the alumina portion serving as the alumina substrate and the yttrium oxide portion serving as the coating; when n=0, the number of the yttrium oxide-aluminum oxide composite ceramic green bodies obtained is 1; when n=1, the number of the yttrium oxide-aluminum oxide composite ceramic green bodies obtained is 2; when n=2, the number of the yttrium oxide-aluminum oxide composite ceramic green bodies obtained is 3; and so on;
[0046] S7, transferring the yttrium oxide-aluminum oxide composite ceramic green body obtained in step S6 to a high-temperature sintering furnace for sintering, and naturally cooling to room temperature in the furnace to obtain a yttrium oxide-aluminum oxide composite ceramic; Figure 3 As shown, since yttrium oxide shrinks too much during the sintering process, it can be found that yttrium oxide is conical after sintering; wherein, the sintering process of the high-temperature sintering furnace includes the following steps:
[0047] S701: the heating rate V is 160-240℃ / min, the temperature is raised to 300℃, and the holding time is th; the temperature is then raised to 400℃ at the heating rate V, and the holding time is th; the temperature is then raised to 500℃ at the heating rate V, and the holding time is th; the temperature is then raised to the sintering temperature T of 1650℃ at the heating rate V, and the holding time is th; at 300℃ to 500℃, the yttrium oxide-aluminum oxide composite ceramic green body is debonded in the furnace, that is, the binder in the yttrium oxide granulated powder and the alumina granulated powder is decomposed and discharged; wherein, the range of t is 1-4h;
[0048] S702: The temperature is cooled from 1650°C to 1000°C at a cooling rate of 2°C / min, and then naturally cooled to room temperature along with the furnace.
[0049] Practice has shown that when the interface formed between the alumina granulated powder and the yttrium oxide granulated powder is located between position A and the upper end surface of the inner cavity of the molding mold or between position B and the lower end surface of the inner cavity of the molding mold, the bonding strength of the yttrium oxide-aluminum oxide composite ceramic obtained therein is poor, and a yttrium oxide-aluminum oxide composite ceramic green body cannot be machined alone; therefore, the interface is preferably located between position A and position B of the molding mold.
[0050] Among them, in step S2 and step S3, the alumina granulated powder and the yttrium oxide granulated powder are quantitatively added respectively, and the "quantity" here refers to the amount of raw material added designed by the technician according to the subsequent cold isostatic pressing, green body machine processing and sintering processes. The "quantity" here can be adjusted by the technician according to different products. The final guarantee is that after the green body machine processing and sintering, the required yttrium oxide-aluminum oxide composite ceramic can be obtained. For example, in one embodiment, a quantitative amount of alumina granulated powder is first added to the forming mold of the cold isostatic press, and the ratio of the added volume of the alumina granulated powder to the volume of the inner cavity of the forming mold is 2:3, and the alumina granulated powder in the forming mold is vibrated and compacted; then, a quantitative amount of yttrium oxide granulated powder is added to the forming mold of the cold isostatic press, and the ratio of the added volume of the yttrium oxide granulated powder to the volume of the inner cavity of the forming mold is 1:3, and the yttrium oxide granulated powder in the forming mold is vibrated and compacted; then, isostatic pressing is performed to obtain a formed ceramic green body. Of course, this implementation is only an example of obtaining one yttrium oxide-aluminum oxide composite ceramic green body. Technicians can also reasonably adjust the amount of raw material added according to the actual shape and material ratio of the product to obtain one or more yttrium oxide-aluminum oxide composite ceramic green bodies after cold isostatic pressing.
[0051] Comparative Example 1
[0052] Comparative Example 1 was used as a blank control group. The coating was obtained by plasma spraying yttrium oxide granulated powder using the existing technology, and an aluminum oxide substrate was selected as the substrate.
[0053] Table 1
[0054]
[0055] Performance Testing
[0056] Test standard:
[0057] (1) The density of composite ceramics shall be in accordance with GB / T5593-1996.
[0058] (2) The bonding strength shall be in accordance with ASTMC1583 / D4541 / D7234 / D7522, ISO4624 / 16276-1, EN1542 / 12004-2, and AS / NZS1580.408.5 standards.
[0059] Table 2
[0060]
[0061]
[0062] It is worth noting that, by comparing Examples 1-11 with Comparative Example 1, the bonding strength of the yttrium oxide-aluminum oxide composite ceramic prepared by the present technical solution is significantly better than the bonding strength of the yttrium oxide coating prepared by the plasma spraying process in the prior art. The bonding strength of the yttrium oxide-aluminum oxide composite ceramic prepared in Example 1 reached 27.55 MPa, far exceeding the bonding strength of the yttrium oxide coating prepared by the prior art, laying a foundation for its application in related alumina ceramic parts of etching machines.
[0063] From the comparison of Examples 1-3, it can be seen that when the cold isostatic pressing pressure increases from 110MPa to 130MPa, the density of the yttrium oxide coating after sintering gradually increases, and the density of the alumina substrate also gradually increases; this indicates that with the gradual increase of the isostatic pressing pressure, the density of the alumina substrate and the yttrium oxide coating is gradually increasing, which is beneficial to improve the strength of the alumina substrate and the yttrium oxide coating. However, with the increase of the cold isostatic pressing pressure, the bonding strength of the yttrium oxide-alumina composite ceramic shows a trend of first increasing and then stabilizing, and when the cold isostatic pressing pressure is 120MPa, its bonding strength reaches the optimal value of 27.55MPa. As the cold isostatic pressing pressure continues to increase, the density of the ceramic green body also continues to increase. When the pressure reaches 120MPa, the density of the ceramic green body has reached its maximum value. At this time, the material strength is excellent and the bonding force is also the highest. When the pressure is less than 120M Pa, the density of the ceramic green body is not enough, the porosity inside the green body is high, and the strength of the material after sintering will also decrease accordingly. When the pressure is greater than 120MPa, the density of the ceramic green body hardly changes (or the density increases very little). Greater pressure requires higher energy and longer time, reducing production efficiency. Therefore, 120MPa is the best applied pressure.
[0064] By comparing Example 1 with Example 4-5, it can be seen that when the holding time of the cold isostatic press increases from 20s to 50s, the density of the yttrium oxide coating after sintering gradually increases as a whole, and the density of the alumina substrate also gradually increases as a whole; this indicates that with the gradual increase in the holding time, the compactness of the alumina substrate and the yttrium oxide coating is gradually increasing, which is beneficial to improving the strength of the alumina substrate and the yttrium oxide coating. However, it can be found that when the holding time exceeds 30s, the density of the yttrium oxide coating and the density of the alumina substrate are basically not increased, indicating that it is most reasonable to set the holding time to 30s. At the same time, with the increase in the holding time, the bonding strength of the yttrium oxide-alumina composite ceramics tends to increase first and then decrease. As the holding time increases, the density of the ceramic green body also increases. When the holding time reaches 30s, the density of the ceramic green body has reached its maximum value. At this time, the material strength is excellent and the bonding force is also the highest. When the holding time is less than 30s, the density of the ceramic green body is not enough, the porosity inside the green body is high, and the strength of the material after sintering will also decrease accordingly. When the holding time is greater than 30s, the density of the ceramic green body hardly changes (or the density increases very little). A longer holding time requires higher energy and more time, which reduces production efficiency. Therefore, 30s is the optimal process parameter.
[0065] By comparing Example 1 and Example 6-7, it can be seen that when the sintering heating rate increases from 160℃ / min to 240℃ / min, the density of the yttrium oxide coating after sintering is first smoothly transitioned and then gradually decreased, and the density of the alumina substrate is also first smoothly transitioned and then gradually decreased. The bonding strength of the yttrium oxide-alumina composite ceramic is first increased and then decreased. When the heating rate is greater than 200℃ / min, due to the excessive heating rate, uneven heating and particle adhesion will occur; the rapid increase in temperature may not provide enough time for the particles to effectively rearrange, resulting in increased porosity and reduced structural density; rapid heating will also produce thermal stress, resulting in microcracks and other defects in the sintered alumina; on the contrary, when the heating rate is too low, the sintering time of the yttrium oxide-alumina composite ceramic green body is extended, and the particles have more sufficient energy to fully react. The prepared material is very dense and has low porosity, but the energy consumed by the slow heating rate will be more.
[0066] By comparing Example 1 with Examples 8-9, it can be seen that when the sintering temperature increases from 1580°C to 1700°C, the density of the yttrium oxide coating, the density of the alumina substrate, and the bonding strength of the yttrium oxide-alumina composite ceramic all show a trend of first increasing and then decreasing. When the sintering temperature is higher than 1650°C, the interior of the yttrium oxide-alumina composite ceramic green body is constantly densified during the sintering process, and the porosity decreases, but at the same time, the grains inside it are also growing synchronously, so the abnormal growth of the grains significantly reduces the strength of the ceramic; when the sintering temperature is lower than 1650°C, the yttrium oxide-alumina composite ceramic green body does not reach densification, has more pores, and the grain growth is incomplete, and the strength of the material will also be significantly reduced.
[0067] By comparing Example 1 with Example 10-11, it can be seen that when the sintering process holding time increases from 1h to 4h, the density of the yttrium oxide coating, the density of the alumina substrate, and the bonding strength of the yttrium oxide-alumina composite ceramic all show a trend of first increasing and then decreasing. When the holding time is less than 2h, the green body does not reach densification, there are many pores, and the grain growth is incomplete, and the strength of the material is significantly reduced. When the holding time is higher than 2h, the inside of the green body is constantly densified, the porosity decreases, but at the same time the grains are also increasing synchronously, so the abnormal growth of the grains significantly reduces the strength of the material.
[0068] Figure 4 From the interface morphology diagram of the yttrium oxide-aluminum oxide composite ceramic prepared in Example 1, it is not difficult to find that yttrium oxide and alumina have undergone mutual embedding at the interface, that is, part of the alumina in the alumina substrate is embedded in the structure of yttrium oxide, and part of the yttrium oxide in the yttrium oxide coating is embedded in the structure of the alumina substrate. This mutual embedding phenomenon effectively improves the bonding strength of the yttrium oxide-aluminum oxide composite ceramic.
[0069] The above embodiments are only used to illustrate the technical solutions of the present disclosure, rather than to limit them. Although the present disclosure has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present disclosure, and they should all be included in the scope of the claims and specification of the present disclosure.
Claims
1. A method for preparing yttria-alumina composite ceramics with high bonding strength, characterized in that: The steps include: S1. Powder raw materials include yttrium oxide granulated powder and aluminum oxide granulated powder; S2, first add a certain amount of alumina granulated powder into a forming mold of a cold isostatic press, and vibrate and compact the alumina granulated powder in the forming mold; S3, adding a certain amount of yttrium oxide granulated powder into a molding die of a cold isostatic press, and vibrating and compacting the yttrium oxide granulated powder in the molding die; S4, repeating steps S2 and S3 n times until the yttrium oxide granulated powder and the aluminum oxide granulated powder fill the entire molding die; wherein n≥0; S5, placing the filled molding die into a cold isostatic press for cold isostatic pressing; S6, machining the formed ceramic green body in step S5 to obtain at least one yttrium oxide-aluminum oxide composite ceramic green body, and machining the yttrium oxide-aluminum oxide composite ceramic green body into a designed shape, with the alumina portion serving as an alumina substrate and the yttrium oxide portion serving as a coating; S7, transferring the yttrium oxide-aluminum oxide composite ceramic green body obtained in step S6 to a high-temperature sintering furnace for sintering, and naturally cooling to room temperature in the furnace to obtain the yttrium oxide-aluminum oxide composite ceramic.
2. The method for preparing the yttrium oxide-aluminum oxide composite ceramic with high bonding strength according to claim 1, characterized in that: In step S1 , the average particle size of the yttrium oxide granulated powder was 38 μm, and the average particle size of the aluminum oxide granulated powder was 57 μm.
3. The method for preparing the yttria-alumina composite ceramic with high bonding strength according to claim 1, characterized in that: In step S3, positions A and B are respectively provided on the forming mold near the upper and lower ends thereof, and an interface is formed between the alumina granulated powder and the yttrium oxide granulated powder, and the interface is located between position A and position B of the forming mold.
4. The method for preparing the yttria-alumina composite ceramic with high bonding strength according to claim 1, characterized in that: In step S5, the cold isostatic pressing pressure P is 110-130 MPa.
5. The method for preparing the yttria-alumina composite ceramic with high bonding strength according to claim 1, characterized in that: In step S5, the holding time m is 20-50s.
6. The method for preparing the yttria-alumina composite ceramic with high bonding strength according to claim 5, characterized in that: In step S5, the holding time m is 20-30s.
7. The method for preparing the yttria-alumina composite ceramic with high bonding strength according to claim 1, characterized in that: In step S7, the sintering process in the high temperature sintering furnace includes the following steps: S701: the heating rate V is 160-240℃ / min, the temperature is raised to 300℃, and the holding time is th; then the temperature is raised to 400℃ at the heating rate V, and the holding time is th; then the temperature is raised to 500℃ at the heating rate V, and the holding time is th; then the temperature is raised to the sintering temperature T of 1650℃ at the heating rate V, and the holding time is th; wherein, the range of t is 1-4h; S702: The temperature is cooled from 1650°C to 1000°C at a cooling rate of 2°C / min, and then naturally cooled to room temperature along with the furnace.
8. The method for preparing the yttria-alumina composite ceramic with high bonding strength according to claim 7, characterized in that: In step S701, the heating rate V is 160-200°C / min, and the holding time t is 2h.
9. A yttrium oxide-aluminum oxide composite ceramic prepared by the method for preparing a yttrium oxide-aluminum oxide composite ceramic with high bonding strength as claimed in any one of claims 1 to 8.
10. Use of the yttria-alumina composite ceramic as claimed in claim 9 in alumina ceramic parts in the inner cavity of an etcher.
Citation Information
Patent Citations
Extending lifetime of yttrium oxide as a plasma chamber material
CN102005352A
Zirconium oxide solid solution yttrium oxide ceramic as well as preparation method and application thereof
CN115124343A
Laminate, corrosion resistant member and halogen gas plasma resistant member
JP2002001865A
Yttria ceramic for plasma process apparatus and method for manufacturing the same
JP2007217218A
Yttria alumina ceramic bonding type window for semiconductor etching process and manufacturing apparatus of the yttria alumina ceramic bonding type window for semiconductor etching process
KR102600456B1
Cited By
Aluminum oxide-yttrium oxide composite ceramic coating and preparation method thereof
CN121202548A